Joining ferrite at a relatively low temperature using 43SnO-15ZnO-35P₂O₅-7SiO₂ phosphate glass braze - Guo, Wei (2022)
Joining ferrite to itself is of great interest for applications in electronic field. Despite the importance, glass joining techniques have been developed to produce reliable joints. In this work, phosphate glass, 43SnO-15ZnO-35P2O5-7SiO2 (in mol.%), was designed and employed to braze ferrite directly in an atmospheric environment at a relatively low temperature (550 ℃, 10 min). The typical microstructure of the ferrite joints was investigated, and the products formed in the joint domain were characterized. The research results indicated that Zn2Mg(PO4)2 phases were produced in the joint domain, and the typical microstructure was ferrite/ Zn2Mg(PO4)2 + glassy phase + Zn2Mg(PO4)2/ferrite. In addition, mechanical properties of the joints were also investigated. The shear test was performed on six brazed samples, and the results showed the joints possessed average strength of 90.2 MP under the joining parameters. Subsequent ffracture analysis indicated the fracture mainly took place at the ferrite side. The present work provides a channel of using phosphate glass for brazing ferrite at low temperatures.